2015
DOI: 10.1515/shll-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short-term study abroad on second language Spanish phonetic development

Abstract: The main aim of the work is to assess physical parameters of forest woodchips and their impact on the prices achieved by the supplier in transactions with a power plant. During fragmentation of logging residue, high content of green matter and contaminants negatively impacts the quality parameters that serve as basis for settlements. The analysis concerns data on the main parameters -water content, fuel value, sulphur and ash content -from 252 days of deliveries of forest chips to a power plant. The deliveries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Nevertheless, it seems unlikely that such a difference would result in almost entirely opposite findings. One other hypothesis, related to Bongiovanni et al (2015), which found the most obvious improvement and differences between the SA and AH groups was in terms of rhotic production, is that, given the dialectal features of the variety spoken in the region in which the present SA students studied abroad, perhaps more attention was dedicated to the production of consonants with salient regional variation to the potential neglect or even detriment of vowel production. Future research that takes into account the specific exposure to, instruction regarding, and attention to pronunciation features during study abroad (as compared to study at home) would assist in teasing apart the influence of these various factors at play during a sojourn abroad.…”
Section: Durationmentioning
confidence: 95%
See 3 more Smart Citations
“…Nevertheless, it seems unlikely that such a difference would result in almost entirely opposite findings. One other hypothesis, related to Bongiovanni et al (2015), which found the most obvious improvement and differences between the SA and AH groups was in terms of rhotic production, is that, given the dialectal features of the variety spoken in the region in which the present SA students studied abroad, perhaps more attention was dedicated to the production of consonants with salient regional variation to the potential neglect or even detriment of vowel production. Future research that takes into account the specific exposure to, instruction regarding, and attention to pronunciation features during study abroad (as compared to study at home) would assist in teasing apart the influence of these various factors at play during a sojourn abroad.…”
Section: Durationmentioning
confidence: 95%
“…Research examining the role of context of learning (and, in the following cases, specifically, the context of study abroad) in L2 development has explored its impact on, for example, morphosyntax (e.g., Collentine 2004;, pragmatics (e.g., Cohen and Shively 2007), and oral fluency (e.g., Freed et al 2004;O'Brien et al 2007; and has found a generally positive effect for time abroad on these areas of linguistic development (e.g., Collentine 2009). Research on the role of context of learning and study abroad on L2 phonological and phonetic development has been, as previously mentioned, somewhat less researched, although work in this area is growing (e.g., Alvord & Christiansen 2012;Bongiovanni et al 2015;Díaz-Campos 2004Lord 2010), and studies in this vein have reported rather modest and inconsistent benefits for the study abroad environment over the at-home context. For example, with regard to development in the production of word-initial /p t k/, Díaz-Campos (2004 and Bongiovanni et al (2015) found that athome and study abroad learners made statistically similar gains over the respective time periods studied (for Bongiovanni et al 2015 gains were only observed for /p/ and /k/, not /t/); Crane (2011) also reported positive results for the study abroad environment in the production of these sounds, but included no at-home comparison group.…”
Section: Context Of Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent to which conclusions can be drawn and compared are limited since the research methods do not ensure that the procedure includes a measure of prior knowledge and maintenance of the features under consideration (George 2014), measuring language contact information abroad (Bongiovanni et al 2015), or learner perceptions of token items (Pope 2016). Müller (2016: 113) reminds her readers that individual learning factors need to be included in the analyses of future studies, which explains why, to date, it has been 'difficult to derive common trends from learner cohorts.…”
Section: Grammatical Competence-phonologicalmentioning
confidence: 99%